Links between contaminant hotspots in low flow estuarine systems and altered sediment biogeochemical processes. (5th November 2017) - Sutherland, Michael D.; Dafforn, Katherine A.; Scanes, Peter; Potts, Jaimie; Simpson, Stuart L.; Sim, Vivian X.Y.; Johnston, Emma L.
Abstract: The urbanisation of coastal zones is a major threat to the health of global estuaries and has been linked to increased contamination (e.g. metals) and excess organic matter. Urban stormwater networks collect and funnel contaminants into waterways at point sources (e.g. stormdrains). Under dry, low flow conditions, these stormwater contaminants can accumulate in sediments over time and result in modifications to benthic sediment biogeochemical processes. To quantify these processes, this field study measured differences in benthic metabolism (CR, GPP, NEM) and sediment-water nutrient fluxes (NH3, NOx, PO4 ) associated with stormdrains (0 m, 200 m and 1000 m away) and increased water-retention (embayments vs channels). Significant changes to benthic metabolism were detected with distance from stormdrains, and with differences in water-retention rates, above natural spatial and temporal variation. Oxygen consumption was ∼50% higher at stormdrains (0 m) compared to 1000 m away and >70% higher at stormdrains (0 m) located in embayments compared to channels. Oxygen production also appeared to decrease with distance from stormdrains in embayments, but patterns were variable. These changes to benthic metabolism were of a magnitude expected to influence benthic nutrient cycling, but NH3, NOx and PO4 fluxes were generally low, and highly spatially and temporally variable. Overall, metal (Cu) contamination explained most of the variation in sediment biogeochemical processes between embayments and channels, while sediment grain size explained differences in fluxes with distance from stormdrains. Importantly, although there was evidence of increased productivity associated with stormdrains, we also detected evidence of early hypoxia suggesting that systems with legacy stormwater contaminants exist on a tipping point. Future work should investigate changes to sediment processes after a major rainfall event, when large and sudden inputs of potentially toxic contaminants occur. Monitoring benthic O2 fluxes could be a sensitive measure of ecological change under these conditions. Graphical abstract: Highlights: Coastal development is a major threat to the estuarine health. Urban contaminants enter estuaries and can modify sediment functions. We measured metabolism and nutrient fluxes in response to contaminant exposures. In situ measures were compared at discharge points between high/low retention. Increased O2 consumption was evident closest to poorly flushed discharge points.